The Legal Status of Artificial Intelligence (AI) Works in the Indonesian Copyright System Based on Law No. 28 of 2014 concerning Copyright - Rozi, Sofi Fahrur; Yuwono, Nikmatul Keumala Nofa (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2025)
The development of artificial intelligence (AI) has brought significant changes to the process of creating intellectual works. AI is now capable of producing various forms of work, from music to scientific papers, without direct human intervention. This raises legal issues regarding the status of AI works in the Indonesian copyright system. Law Number 28 of 2014 concerning Copyright requires a legal subject in the form of a creator who has the ability and will to create. Because AI is not a legal subject and does not have a will like humans, there is uncertainty as to whether its works can be protected within the national copyright legal framework. This article examines the legal status of AI works from the perspective of the Copyright Law and offers a legal approach that allows for the protection of works produced by AI technology. This study aims to contribute to the formation of a legal framework that is responsive and adaptive to advances in digital technology.